Clinical and Genetic Spectrum of Nine Cases of NLRP3-Associated Autoinflammatory Disease (NLRP3-AID) and Identification of One Novel NLRP3 Mutation by Genetic Variation Analyses - Yaoyao Shangguan; Xingru Ding; Le Ma; Yi-Xin Cai; Shulei Xiang; Xiu-Feng Huang; Yunyan Shen; Hai-Guo Yu; Wenjie Zheng (Journal of Immunology Research)
Purpose. NLRP3-associated autoinflammatory disease (NLRP3-AID) is characterized by gain-of-function variants in the NLRP3 gene. Since there are little literature focusing on pediatric NLRP3-AID in China, we aimed to elucidate the phenotypic and genotypic profiles of Chinese patients with NLRP3-AID. Methods. Patients with NLRP3-AID at three rheumatology centers in China were genotyped through whole exome sequencing or gene panel sequencing. Sanger sequencing was performed on all patients and their parents. Clinical phenotype, treatment, and prognosis were analyzed. Results. Nine patients with NLRP3-AID were enrolled between December 2014 and October 2022 with an average follow-up period exceeding 30 months. The median age of onset was 12 months, and 66.7% were younger than 3 years old. The diagnosis was significantly delayed and the median delay duration was 115 months. The patients most commonly presented with rash (100%), arthritis/arthralgia (88.9%), lymphadenopathy (88.9%), fever (77.8%), and growth retardation (44.4%). During acute attack, white blood cell, C-reactive protein, and/or erythrocyte sedimentation rate all increased in all cases, and inflammatory markers remained elevated beyond 7 days postfever resolution in 57.1% of patients (4/7). Two cases of chronic infantile neurological cutaneous articular syndrome (CINCA) had clubbed fingers, one with interstitial lung disease, a finding rarely reported. Treatment with glucocorticoids (77.8%) and biologic agents (33.3%) yielded 66% complete remission and 33% partial remission. Genetic analysis identified eight pathogenic NLRP3 missense mutations, including one novel mutation. Conclusions. Our study illuminated the distinct clinical and genetic features of Chinese NLRP3-AID patients, emphasizing the significance of early genetic screening. Despite delayed diagnosis, treatment primarily with glucocorticoids and biologic agents, led to favorable outcomes. Genetic heterogeneity, including a novel mutation, highlighted the complexity of NLRP3-AID in this population.